Managing Metabolic Dysfunction-associated Steatotic Liver Disease (MASLD) in Primary Care Settings: A Review - Vignesh Rajan; Ambarish Das; J. Venkatachalam; K. K. Lohani; Chandrakant Lahariya (Preventive Medicine: Research & Reviews, 2025)
This review article discusses and summarises metabolic dysfunction-associated steatotic liver disease (MASLD) from the perspective of primary healthcare physicians. It also outlines the approach to prevent and care and when to refer to the next level of facility. The article discusses the prevention of MASLD through proven interventions such as lifestyle modifications, including dietary changes, physical activity and treatment with certain anti-diabetic medications, which are effective in preventing disease progression. The actionable strategies for primary care providers include implementing targeted health education programmes, conducting regular screenings for at-risk populations and promoting healthy lifestyle changes through community engagement initiatives. In addition, policy interventions, such as integrating MASLD screening into national health programmes and ensuring access to affordable treatment options, are crucial for mitigating the long-term health impacts of this disease.